Evaluation of iron-folic acid supplementation in young women in Mataram City - Kantari, Eka Suci; Huriyati, Emy; Penggalih, Mirza Hapsari Sakti Titis (BKM Public Health and Community Medicine, 2022)
Purpose: The government program to prevent iron deficiency anemia in adolescent girls provides iron-folic acid supplementation, usually known as TTD or "Tablet Tambah Darah". The number of adolescent girls who received TTD was 76.2%, whereas 80.9% were given at school, and the rest were from other sources. The obedience of young women to consuming TTD is one factor that affects the effectiveness of the TTD program. Methods: This research was a cross-sectional study of a non-experimental design survey. The study sample was 159 people, 15-to 18-year-old adolescent girls of SMAN 5 Mataram. Results: Bivariate analysis showed that attitudes and obstacles were not statistically related to compliance, as seen from the attitude value p-value = 0.052 and resistance p-value 0.135. Obstacles have a relationship with attitudes with a value of p = 0.01. Conclusion: Attitudes and obstacles have no relationship to obedience in adolescent girls, while obstacles have a relationship with attitudes towards adolescent girls.